Strategi Guru dalam Mengatasi Kesulitan Belajar Matematika pada Siswa SD Berdasarkan Teori Behavioristik - Nurhudayah Manjani; Mardiyah Kharismayanda; Sela Maranata; Sartika Putri Ruth Angel Sihombing; Yoel Martua Sipahutar (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research aims to explore the ways in which teachers address the challenges of learning mathematics for children in primary schools by referring to behavioristic theory. This theory emphasizes the central role of stimuli and reactions in influencing learning behavior, and the application of both positive and negative reinforcement to improve students' motivation and understanding. The approach adopted was a descriptive qualitative method using case studies in various primary schools. The results indicated that behavior-focused methods, such as providing repeated practice of problems, immediate feedback, use of concrete tools, and regular application of rewards and punishments, can improve students' enthusiasm and mathematics learning outcomes. However, teacher-driven learning and lack of innovation are barriers to implementation. Therefore, a combination with other methods is needed to make the learning process more thorough.